2008
DOI: 10.1007/s10750-008-9390-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of flood pulses on diet composition and trophic relationships among piscivorous fish in the upper Paraná River floodplain

Abstract: The aim of this article is to evaluate whether alterations in flood pulses differentially affect diet composition, feeding niche breadth, and diet overlap of piscivorous fish. Species examined were Acestrorhynchus lacustris, Hoplias aff malabaricus, Plagioscion squamosissimus, Rhaphiodon vulpinus, and Salminus brasiliensis. These species were collected with gillnets (different mesh sizes) in the upper Paraná River floodplain, during four distinct flood events (four periods; A = 1992/ 1993; B = 2000; C = 2001; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 35 publications
3
56
0
2
Order By: Relevance
“…H. aff. malabaricus is an ambush predator, selectively occupying sites with high structural complexity, such as macrophyte banks, where prey abundance tends to be high, thus increasing success of prey capture (Luz- Agostinho et al, 2008), as observed in the present study during the 2006 rainy season. Aquatic macrophytes play an important role in lowland lakes by increasing microhabitat heterogeneity and, consequently, resources for prey (i.e.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…H. aff. malabaricus is an ambush predator, selectively occupying sites with high structural complexity, such as macrophyte banks, where prey abundance tends to be high, thus increasing success of prey capture (Luz- Agostinho et al, 2008), as observed in the present study during the 2006 rainy season. Aquatic macrophytes play an important role in lowland lakes by increasing microhabitat heterogeneity and, consequently, resources for prey (i.e.…”
Section: Discussionsupporting
confidence: 52%
“…As native predators can decrease Factors such as habitat preference, environmental conditions, prey size and mobility can play a major role on selectivity than prey abundance (Luz- Agostinho et al, 2008;Milani et al, 2010). H. aff.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies of the effect of annual variation in water level on the diet of fish in this region have been carried out (Almeida et al, 1997;Hahn et al, 2004;Russo, 2004;Luz-Agostinho et al, 2008). However, studies on the effects of the inter-annual variation of the flood re-ated by the regressions between the logarithms of total weight (Wt) and standard length (Ls), by species.…”
Section: Introductionmentioning
confidence: 99%
“…The literature also contains several studies examining the effect of the annual variation in water level on fish diet in the region (Almeida et al, 1997;Hahn et al, 2004;Russo, 2004;Luz-Agostinho et al, 2008) or the effect of regulation and nutrient retention on the food chain length (Hoeinghaus et al, 2008) and carbon flow patterns (Hoeinghaus et al, 2007). Studies on the effects of interannual variations in the flooding regime, especially on a scale involving periods prior to and following the construction of Porto Primavera Reservoir, on aspects related to food intake intensity and fish condition are nonexistent.…”
Section: Introductionmentioning
confidence: 99%